Pedestrian Facility Needs Analysis at the Faculty of Engineering Campus, Sultan Ageng Tirtayasa University - Ujianto, Rifky; Syahid, Mush'ab Abdu Asy; Intari, Dwi Esti; Budiman, Arief; Irlana, Zidan (JURUSAN TEKNIK SIPIL, 2024)
This research discusses pedestrian facilities at the Faculty of Engineering Campus of Sultan Ageng Tirtayasa University located in Cilegon City, there are no adequate pedestrian facilities so it is necessary to analyze pedestrian facilities which aim to determine the type of pedestrian facilities used at the Faculty of Engineering Campus of Sultan Ageng Tirtayasa University and create a pedestrian facility design at the Faculty of Engineering Campus of Sultan Ageng Tirtayasa University. Analyzing the needs of this pedestrian facility uses guidelines from the Ministry of PUPR Regarding Technical Planning of Pedestrian Facilities in 2018 and to design pedestrian facilities using sketchup software. The result of this study is that the pedestrian facilities produced in the form of a pelican cross based on the formula produces on average with P = 79 people / hour, V = 8461 (vehicles / hour) then produce is (6 x ) and the effective width of the sidewalk inside the Faculty of Engineering Campus of Sultan Ageng Tirtayasa University is 1.5 meters, these results are adjusted to the 2018 Ministry of PUPR guidelines.